Methods for Identifying Specific Language Impairment in Bilingual Populations in Germany - Hamann, Cornelia; Abed Ibrahim, Lina (Frontiers in Communication, 2017)
This study investigates the performance of 22 monolingual and 54 bilingual children with and without specific language impairment (SLI), in a nonword repetition (NWRT) and a sentence repetition task (SRT). Both tasks were constructed according to the principles for LITMUS tools (Language Impairment Testing in Multilingual Settings) developed within COST Action IS0804, and incorporated phonological or syntactic structures that are linguistically complex and have been shown to be difficult for children with SLI across languages. For phonology these are in particular (non)words containing consonant clusters. In morphosyntax complexity has been attributed to factors such as embedding and/or syntactic movement. Tasks focusing on such structures are expected to identify SLI in bilinguals across language combinations. This is notoriously difficult because structures that are problematic for typically developing bilinguals (BiTDs) and monolingual children with SLI (MoSLI) often overlap. We show that the NWRT and the SRT are reliable tools for identification of SLI in bilingual contexts. However, interpretation of the performance of bilingual children depends on background information as provided by parental questionnaires. In order to evaluate the accuracy of our tasks we recruited children in ordinary kindergartens or schools and in Speech Language Therapy centers and verified their status with a battery of standardized language tests, assessing bilingual children in both their languages. We consider a bilingual child language impaired if she shows impairments in two language domains in both her languages. For assessment we used tests normed for monolinguals (with one exception) and adjusted the norms for bilingualism and for language dominance. This procedure established the following groups: 10 typical monolinguals (MoTD), 12 MoSLI, 46 BiTD and 8 bilingual children with SLI (BiSLI). Our results show that both tasks target relevant structures: monolingual children are classified with 100% accuracy. Crucially, both our tasks distinguish BiTDs from MoSLIs and BiTDs from BiSLIs. The NWRT shows high accuracy and only minimal influence of language dominance. The SRT can be scored as “identical repetition” or as “target structure”, the latter aiming for scoring the mastery of a syntactic structure, ignoring lexical and specific case or gender errors. Focusing on the latter measure, we